Akibat Hukum Dissenting Opinion terhadap Putusan Pengadilan dalam Perkara Tindak Pidana Korupsi - Susiana Kifli (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The corruption court which was shaped dependent on Law No. 46 of 2009, practically speaking has applied numerous choices chosen by leading Disagreeing Assessment, this alludes to the situation of the Debasement Court as an uncommon court actually dependent upon the Legal Force Act which permits Contradicting Assessment, or for judges who have various conclusions can contain his viewpoint in the choice was the substance of the choice looking into it of a criminal demonstration of defilement. The issues talked about in this paper is: What is the lawful impact of disagreeing assessment on court choices in instances of defilement? This examination is a legitimate exploration with standardizing juridical methodology as the primary methodology in investigating lawful material. In view of the consequences of the examination and conversation, the accompanying ends can be drawn: 1). Because of the utilization of the contradicting assessment to the Adjudicators' choice since the authorization of Law Number 4 of 2004 concerning Legal Force, there is a show among individuals from a board of judges where if in a pondering meeting the board of judges isn't arrived at agreement, the assessment of a minority judge not the same as the consequence of a legal gathering should be remembered for the choice and is a section which is indivisible from the choice. Contradicting feelings can likewise be utilized as thought for decided at the allure and cassation level.